Abrupt ice-age shifts in southern westerly winds and Antarctic climate forced from the north. (29th November 2018) - Buizert, Christo; Sigl, Michael; Severi, Mirko; Markle, Bradley; Wettstein, Justin; McConnell, Joseph; Pedro, Joel; Sodemann, Harald; Goto-Azuma, Kumiko; Kawamura, Kenji; Fujita, Shuji; Motoyama, Hideaki; et al.
Abstract The mid-latitude westerly winds of the Southern Hemisphere play a central role in the global climate system via Southern Ocean upwelling1, carbon exchange with the deep ocean2, Agulhas leakage (transport of Indian Ocean waters into the Atlantic)3 and possibly Antarctic ice-sheet stability4 . Meridional shifts of the Southern Hemisphere westerly winds have been hypothesized to occur5, 6 in parallel with the well-documented shifts of the intertropical convergence zone7 in response to Dansgaard–Oeschger (DO) events— abrupt North Atlantic climate change events of the last ice age. Shifting moisture pathways to West Antarctica8 are consistent with this view but may represent a Pacific teleconnection pattern forced from the tropics9 . The full response of the Southern Hemisphere atmospheric circulation to the DO cycle and its impact on Antarctic temperature remain unclear10 . Here we use five ice cores synchronized via volcanic markers to show that the Antarctic temperature response to the DO cycle can be understood as the superposition of two modes: a spatially homogeneous oceanic 'bipolar seesaw' mode that lags behind Northern Hemisphere climate by about 200 years, and a spatially heterogeneous atmospheric mode that is synchronous with abrupt events in the Northern Hemisphere. Temperature anomalies of the atmospheric mode are similar to those associated with present-day Southern Annular Mode variability, rather than the Pacific–South American pattern. Moreover, deuterium-excess records suggest a zonally coherent migration of the Southern Hemisphere westerly winds over all ocean basins in phase with Northern Hemisphere climate. Our work provides a simple conceptual framework for understanding circum-Antarctic temperature variations forced by abrupt Northern Hemisphere climate change. We provide observational evidence of abrupt shifts in the Southern Hemisphere westerly winds, which have previously documented1–3 ramifications for global ocean circulation and atmospheric carbon dioxide. These coupled changes highlight the necessity of a global, rather than a purely North Atlantic, perspective on the DO cycle. The position of the Southern Hemisphere westerly winds responds immediately to abrupt North Atlantic climate events of the last ice age, with a spatially heterogeneous impact on Antarctic climate.